Effect of Ni–Co codoping on structure and electrical properties of multiferroic BiFeO3 nanoparticles. (1st July 2013) - Hossain, Sk Mazaffar; Mukherjee, Ayan; Basu, Soumen; Pal, Mrinal
Abstract : Ni and Co doped nanocrystalline BiFeO3 (BFO) have been prepared using a facile sol–gel technique. The effects of codoping on the crystal structure, morphology and electrical properties are investigated. X‐ray diffraction and high‐resolution transmission electron microscopy studies confirm the phase purity and growth of BFO nanoparticles. The heat‐flow measurement using a differential thermal analyser shows an endothermic peak between 1070 and 1100 K representing ferroelectric to paraelectric phase transition. A systematic electrical conductivity study of these nanoparticles delineates that resistivity increases for doped BFO samples which is very much desirable for device applications of multiferroics.